2020
DOI: 10.22416/1382-4376-2020-30-2-35-44
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Microbiota in Patients with Chronic Heart Failure and Systolic Dysfunction

Abstract: Aim. To study the composition of the intestinal microbiota in patients with chronic heart failure (CHF), as well as a relationship between the features of the CHF clinical course and changes in the microbial composition of the colon.Materials and methods. The study included 60 heart failure patients with systolic dysfunction diagnosed according to the results of echocardiographic examination. The control group consisted of 20 patients comparable to the main group by gender, age and underlying diseases in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…These results reflect those of Fadeeva M.V. et al (2020) who also found that an increase in the proportion of Methanobacteriaceae in heart failure patients with systolic dysfunction [ 36 ]. According to the results of 16S RNA sequencing analysis, gut microbiota composition in ASCVD group was associated with relatively decreased Sutterellaceae, in turn, the HFrEF group was associated with a relatively increased abundance of the same family at the same time with the increasing abundance of Erysipelotrichaceae.…”
Section: Discussionsupporting
confidence: 89%
“…These results reflect those of Fadeeva M.V. et al (2020) who also found that an increase in the proportion of Methanobacteriaceae in heart failure patients with systolic dysfunction [ 36 ]. According to the results of 16S RNA sequencing analysis, gut microbiota composition in ASCVD group was associated with relatively decreased Sutterellaceae, in turn, the HFrEF group was associated with a relatively increased abundance of the same family at the same time with the increasing abundance of Erysipelotrichaceae.…”
Section: Discussionsupporting
confidence: 89%